Pengembangan Usaha UMKM Dengan Menggunakan Analisis Profit Planning Pada UMKM Di Kabupaten Kampar - Mudrika Alamsyah; Suci Nurulita (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2020)
The purpose of this Community Service is to provide training on MSME Business Development Using Profit Planning Analysis aimed at MSME managers (businesses with micro, small and medium scope) in Kampar Regency. This training is needed so that MSME managers have ability to calculate all costs in their respective MSMEs, starting from determining production costs, marketing and administration costs. After that, the profit target to be achieved is determined so that the profit planning can be analyzed. This training really helps MSMEs so that these businesses know whether their activities are already in the expected profit or are still in a loss or return on investment. The method of implementation is by providing training materials, practice questions and finally self-counting exercises in their respective UMKM cases. In the final test results, it can be seen that there is additional knowledge of MSME managers after the training is given. It is hoped that after this training, the knowledge gained can be applied in MSME businesses so that they can increase income and develop MSME businesses.